Recent Developments and Key Considerations Impacting the Operations of One-Stop Shops for Citizens : A Summary of Major Trends and a Design Guide for Citizen Service Centers - Pfeil, Helene; Schott, Berenike; Agarwal, Sanjay (World Bank, Washington, DC, 2017)
Countries across the globe are establishing new and improving existing citizen service centers (CSCs) to better serve their citizens. This note provides an overview of recent developmentsimpacting CSC operations as well as a CSC design guide meant to summarize essential issues that managers looking to establish CSCs may wish to consider. Part 1 lays out how four key themes—access, personalization, speed, and interaction—have shaped the latest innovations in citizenservice center design. These themes are linked to the increasing availability and spread of new technologies, which open new channels for governments to provide information and services to their citizens, and expand the potential for multichannel approaches. Based on these trends, part 2presents a CSC design guide which provides an overview of eight key issues to take into account when designing or reforming a CSC: (1) channels of service delivery; (2) depth of service delivery; (3) financing models; (4) organizations involved and breadth of services provided; (5) single or multiple windows; (6) homogeneity/diversity across CSCs; (7) location; and (8) if services are provided by target group, life event or category of service.